Seismic deformation styles in the upper and lower plate domains of the Calabrian subduction zone, south Italy. (May 2021) - Orecchio, Barbara; Neri, Giancarlo; Presti, Debora; Scolaro, Silvia; Totaro, Cristina
Highlights: Seismic faulting style changes from upper to lower plate of Calabrian subduction zone. Lithospheric strain shows puzzle distribution at edges of Calabrian subducting slab. Rotation and residual subduction of Ionian lithosphere control strain in Calabria. Abstract: We analyzed waveform inversion focal mechanisms of earthquakes that occurred in the last decades in the Calabrian Arc region, the most seismic area of Italy according to historical catalogs and the only where active subduction can be still found along the Nubia-Eurasia convergent margin. We focused our analysis on earthquakes shallower than 40 km and, in order to reduce the effects of very local scale processes, with magnitude 4.0 and larger. Hypocenters of the individual earthquakes with their uncertainties have been compared with location and geometry of the Calabrian Subduction Interface (CSI), reconstructed by previous investigators, with the purpose of associating the individual earthquakes and their focal mechanisms to the shallower part of the Ionian subducting plate (lower plate) or to the Tyrrhenian overriding plate (upper plate). By integrating focal mechanisms available from literature and catalogs with those properly estimated in this study we obtained a dataset of 31 focal mechanism solutions. Considering the focal depth of each earthquake and the CSI depth in the relative epicentral area, only one of the selected earthquakes could not be univocally associated to one of the two domains (lower or upper plate). The other 30 FMs show an evident west-east separation between the western earthquakes of the Tyrrhenian Sea and mainland Calabria occurring in the upper plate domain (17 earthquakes), and the eastern ones of the Calabria Ionian shore and relative offshore occurring in the lower plate domain (13 earthquakes). The focal mechanism distribution highlights clear extension in the Tyrrhenian overriding plate with opening direction trending roughly perpendicular to the Calabrian Arc mountain chain. The situation appears quite more complex in the Ionian lower plate where seismic faulting indicates marked heterogeneity with prevailing compressional features. These results are discussed together with the information available in the literature for the study area concerning historical earthquakes and relative sources, tectonic stress distributions, geodetic crustal velocities and related strain rates. Finally, we comment our findings in the light of recent geodynamic models proposed in the literature for the same area and for the wider central Mediterranean region.